Ranking with Partial Information: A Method and an Application - Kirkwood, Craig W.; Sarin, Rakesh K. (Operations Research, 1985)
A method is presented for ranking multiattributed alternatives using a weighted-additive evaluation function with partial information about the weighting (scaling) constants, the method is applied to evaluate materials for use in nuclear waste containment. The paper derives conditions to determine whether a pair of alternatives can be ranked given the partial information about weighting constants, and presents an algorithm that partially rank-orders the complete set of alternatives based on the pairwise ranking information.